Quantitative absorption imaging of red blood cells to determine physical and mechanical properties. Issue 64 (23rd October 2020) - Paul, Ratul; Zhou, Yuyuan; Nikfar, Mehdi; Razizadeh, Meghdad; Liu, Yaling
Abstract : The constant thickness in the microfluidic channel is used for controlled absorption of red and blue light to measure red blood cell hemoglobin and height mapping. High speed recording of the height mapping provides us the membrane fluctuation. Abstract : Red blood cells or erythrocytes, constituting 40 to 45 percent of the total volume of human blood are vesicles filled with hemoglobin with a fluid-like lipid bilayer membrane connected to a 2D spectrin network. The shape, volume, hemoglobin mass, and membrane stiffness of RBCs are important characteristics that influence their ability to circulate through the body and transport oxygen to tissues. In this study, we show that a simple two-LED set up in conjunction with standard microscope imaging can accurately determine the physical and mechanical properties of single RBCs. The Beer–Lambert law and undulatory motion dynamics of the membrane have been used to measure the total volume, hemoglobin mass, membrane tension coefficient, and bending modulus of RBCs. We also show that this method is sensitive enough to distinguish between the mechanical properties of RBCs during morphological changes from a typical discocyte to echinocytes and spherocytes. Measured values of the tension coefficient and bending modulus are 1.27 × 10 −6 J m −2 and 7.09 × 10 −20 J for discocytes, 4.80 × 10 −6 J m −2 and 7.70 × 10 −20 J for echinocytes, and 9.85 × 10 −6 J m −2 and 9.69 × 10 −20 J for spherocytes, respectively. This quantitative light absorption imaging reduces the complexity related to the quantitative imaging of the biophysical and mechanical properties of a single RBC that may lead to enhanced yet simplified point of care devices for analyzing blood cells.